Load-bearing capacity of compressed concrete elements subjected to repeated load strengthened with CFRP materials - Trapko, Wojciech; Trapko, Tomasz (Journal of Civil Engineering and Management, 2012)
This paper presents the results of experimental investigations of compressed concrete elements behaviour subjected to monotonic and cyclic load strengthened with CFRP materials. Two types of CFRP strengthening were applied during the experiment – longitudinal strips and/or transverse sheets. The results obtained allowed to draw conclusions concerning the possibility of representing a stress-strain monotonic curve with a curve of cyclic strains. The influence of load history on strain parameters of the investigated elements was found. The influence of the strengthening pattern and the state of effort on Young modulus and residual strains was analyzed. Moreover, observations were made of the disadvantageous effect of cyclic loads on strengthening durability, which lead to deformation or partial delamination of external CFRP reinforcement.